Experimental tendon rehabilitation model, histologic stages of healing associated with tensile strength restoration - Abdulaqadir, Shang Ziyad; Hassan, Abdullah Othman; Rashid, Rzgar Farooq; Hassan, Rawaz Rizgar (International Journal of Advanced Engineering Research and Science, 2021)
The tendon repair process is the focus of a lot of current study. It is common to use histological and biomechanical tests to evaluate various gene therapy and tissue engineering procedures. There is some overlap between the two methods, but they have historically been viewed as two distinct things. To compare data from different research or even within the same study, there is no approved scoring scale for histological examination. Biomechanical testing can produce reliable results, but it comes at a higher price and requires more time and effort. An objective, verified scoring system for histological results and biomechanics was anticipated to be the best way to compare histolog ical findings. Histological grading scale for assessing tendon repair has been devised in Achilles tendon model. Angiogenesis, collagen orientation, and cartilage induction are graded by the system. Histology scores were plotted against biomechanical testing findings of healing tendons, and the results showed a strong linear association between histological qualities and biomechanical characteristics. Concurrently, this study presents a practical and financially possible way to evaluate repair while accounting for both the histology and biomechanical features observed in surgically repaired, regenerating tendon.